Gold and green forests : Crafted life stories about Canadian Goldenrod and elm trees - Arvidsson, Anna-Karin (FormAkademisk, 2023)
Sweden's fauna and flora are constantly changing. Humans have not only deliberately promoted and introduced new species in horticulture, agriculture and forestry, they have also acted as a vector for the introduction of alien species through, for example, transportation and food. When these species spread rapidly and affect biodiversity, they are deemed ‘invasive alien species’. This artistic research project explores and articulates how humans, as part of a system where nature and culture meet, affect complex functioning ecosystems through the movement of species. The starting point is the iconic elm tree and how its cultural and natural ecosystems have been wiped out in large parts of Europe by the invasive fungus Ophistoma novo ulmi. With the extinction of the elm come ecological and cultural losses. Those losses are examined and interpreted in this work, in a dialogue with nature and with people. At the same time, another species is explored, the Canadian goldenrod, which, unlike the elm, is expanding rapidly. With these explorations, life stories about the elm will be created not only for our collective memory, but also for speculation about what happens when a new and invasive alien species, such as the Canadian goldenrod, spreads. The form of my narrative is based in materials, crafts and objects. It is primarily the objects and the process that are the carriers of the stories. As a ceramicist, I use clay as a sketching material, binder and a tool for documentation. These species, the elm and the goldenrod, constitute the materiality that are part of the exploration and creation.